Leader-follower attitude consensus for a network of boundary-controlled flexible spacecraft - Takahiro ENDO; Yuki MORIMOTO (Mechanical Engineering Journal)
In future space missions, cooperative attitude control is required for essential tasks with multiple spacecraft, such as satellite constellations. In recent years, spacecraft have increased in size and weight, necessitating infinite-dimensional systems. This paper discusses a leader-follower attitude consensus control of a multiagent system with multiple flexible spacecraft. Each flexible spacecraft consists of two flexible structures and a rigid hub, and its dynamic behavior is given by a hybrid PDE-ODE model. For this controlled system, to achieve attitude consensus control and suppress the elastic vibration of the system simultaneously, we propose a distributed boundary controller and show that the controller exponentially stabilizes a closed-loop system. We also investigate the closed-loop system’s stability in the context of varying communication topologies and in the presence of disturbances. Finally, we carried out numerical simulations to validate the effectiveness of the proposed controller.